Land Dispute and Traditional Customs in the New Territories: Analysis of Tang Kwong Yu Tong Case - Shen, Han (Transactions on Social Science, Education and Humanities Research, 2024)
In this paper, one of the most important methodologies is the literature analysis, that is, the use of legal provisions and the original text of the judgment as the basis for the interpretation of the Tang Kwong Yu Tong case. Since the second half of the last century, a large number of scholars have been critical of the present-day land administration and traditions in Hong Kong, which have been regarded as a travesty of the law. However, an inquiry into the reasons for the existence of this custom in judicial practices requires not only legal analysis, but also consideration of the historical background. As a legal history paper, this paper will investigate the causes of land custom and the reasons for its continuation to the present day by combining case studies with historical knowledge. Despite the irrationalities and anachronisms of traditional land practices, these customs are bound to exist for a long period.